Ternary semitransparent organic solar cells with a laminated top electrode. Issue 1 (1st January 2017) - Makha, Mohammed; Testa, Paolo; Anantharaman, Surendra Babu; Heier, Jakob; Jenatsch, Sandra; Leclaire, Nicolas; Tisserant, Jean-Nicolas; Véron, Anna C.; Wang, Lei; Nüesch, Frank; Hany, Roland
Abstract: Tinted and colour-neutral semitransparent organic photovoltaic elements are of interest for building-integrated applications in windows, on glass roofs or on facades. We demonstrate a semitransparent organic photovoltaic cell with a dry-laminated top electrode that achieves a uniform average visible transmittance of 51% and a power conversion efficiency of 3%. The photo-active material is based on a majority blend composed of a visibly absorbing donor polymer and a fullerene acceptor, to which a selective near-infrared absorbing cyanine dye is added as a minority component. Our results show that organic ternary blends are attractive for the fabrication of semitransparent solar cells in general, because a guest component with a complementary absorption can compensate for the inevitably reduced current generation capability of a high-performing binary blend when applied as a thin, semitransparent film. Abstract :